The Comprehensive overview of the recent advancements in self-healing asphalt utilizing nano-technology - Wondimagegne Mamo Mengistu; Abera Ambaye; Anwar Beshir Mohammed; Nefisa Abdulkadir; Wubeshet Gebru (Ethiopian Journal of Science and Sustainable Development)
Because of factors like age, wear and tear, and elements such as rain, sunlight and chemicals that come into contact with the pavement surface, traditional asphalt materials are vulnerable to degradation. To overcome this, nanotechnology is used, preferred by its self-healing mechanisms that can patch cracks and preserve the structural integrity of the material. The main goal of this review is to give a thorough overview of the recent developments in nanotechnology-based self-healing asphalt. Recent articles, all of which are published in web of science indexed journals, are used. The utilization of nano-fillers, which can be incorporated into the asphalt matrix to improve its mechanical characteristics and self-healing capacity is highlighted in the review. When cracks appear, the large surface area and reactivity of these materials help to speed up the healing process. The review also addressed the function of encapsulated healing agents that are distributed throughout the asphalt binder, such as rejuvenators and rejuvenating microcapsules. These healing chemicals are released when a crack forms and work to fix the damage, essentially by restoring its integrity. In conclusion, self-healing asphalt that makes use of nanotechnology has shown to have a great deal of promise for durable and sustainable asphalt pavements. Incorporating nano-fillers with encapsulated healing agents has demonstrated encouraging outcomes in terms of enhancing the mechanical properties of the material and repairing cracks. To maximize the healing efficiency, to create standardized testing procedures, and to handle the practical difficulties in widely implementing self-healing asphalt, further studies are needed.